Efeitos respiratórios, musculares e autonômico do protocolo fisioterapêutico realizado durante hemodiálise em indivíduos com insuficiência renal crônica - SIMÕES, Mayara (2018)
BACKGROUND: Chronic Renal Insufficiency (CRI) affects several physiological systems, being responsible for the increasing number of morbidity and mortality in this population. The objective of this study was to analyze whether the proposed physiotherapeutic protocol during hemodialysis (HD) increases the strength of knee extensors, palmar grip and respiratory muscles, lung function, functional capacity and modifies autonomic heart rate (HR) modulation of individuals with CRI. METHODS: A quasi-experimental study of the before and after type, in which the physiotherapeutic intervention was performed in individuals with CRI undergoing HD. Participants were submitted to the protocol, performed in the first two hours of the HD, three times a week for eight weeks, consisting of respiratory exercises, aerobic exercises, and electrostimulation associated with resistance exercises. Variability of heart rate (HRV), respiratory muscle strength, strength knee extensors and palmar grip strength, lung function and functional capacity were analyzed before and after intervention. The level of significance was set at 5%. RESULTS: Eleven individuals (49.2 ± 8.6 years) participated in the study. There was a significant increase in RRtri index (p = 0.037), maximal length of diagonal lines (p = 0.044), expiratory muscle strength (p = 0.012), strength of knee extensors (p = 0.025), palmar grip (p = 0.001), and functional capacity (p = 0.009). CONCLUSION: The proposed protocol modifies the autonomic modulation of HR, and is effective in increasing expiratory muscle strength, knee extensors and palmar grip, as well as the functional capacity of individuals with CRI in HD.